Compressive Strength of Concrete Containing Laterite Stone and Palm Oil Clinker as Fine Aggregate Replacement. Issue 1 (February 2021) - Shahid, K A; Muthusamy, K; Ghazali, N
Abstract: The high dependency of construction industry on supply of river sand has initiated research to find other alternative materials that can be used as partial sand replacement in concrete production. Two types of material, that is palm oil clinker (POC) which continuously produced waste from local palm oil industry and freely available laterite aggregate on earth surface have been investigated its potential to be used as partial sand replacement in concrete. The present research was carried out to determine the workability and compressive strength of concrete containing laterite aggregate and crushed palm oil clinker as partial fine aggregates replacement. Concrete mixes have been prepared by integrating various proportions of laterite aggregate and palm oil clinker by weight of river sand. The compressive strength test was conducted on the continuously water cured specimens at 7, 14 and 28 days. The results showed a perfect combination of fine laterite and fine palm oil clinker on S1 (25% of FL + 25% of FPOC) as partial fine aggregate replacement contributed towards enhancement of concrete strength.